The Person Competent to Appeal: Canon 1628 - Mendonça, Augustine (CLSA advisory opinions, 2001-2005, 2001)
In a marriage nullity case, the petitioner ordinarily seeks from a tribunal a declaration of invalidity of his or her marriage. Because an affirmative decision in such a case is in favor of the petition, the one pleading for it cannot be considered harmed in any way by such a decision. Nevertheless, can a petitioner legitimately appeal such a decision?